Rice crop residue as fertiliser substitute for enhancing yield and soil health: Identifying the optimum level from multilocation trials in India - Rajendran, Gobinath; Shanmugam, Vijayakumar; Lakshminarayanan, Aruna; Aabid Hussain, Lone; Joseph, Biju; Kumar, Vipin; Pant, Anil Kumar; S, Ajith; MBB, Prasad Babu; Rapolu, Mahendra Kumar; Raman Meenakshi, Sundaram (Frontiers in Soil Science, 2025)
To address agricultural challenges like residue burning and excessive inorganic fertilizer use, a two-year (2023–2024) multi-location field experiment was conducted across five diverse Indian agro-ecological zones. Six integrated nutrient management strategies were tested: T1 (100% Recommended Dose of Fertilizers (RDF)), T2 (50% RDF + 50% RDF via residue), T3 (50% RDF + 50% RDF via residue + Pusa decomposer (PD)), T4 (50% RDF via residue + 50% RDF via green manure/green leaf manure), T5 (75% RDF + 25% via residue + PD), and T6 (control). Conventional fertilization (T1) consistently achieved the highest mean grain yield across locations. However, T5 (25% RDF substitution via crop residue) produced statistically comparable yields to T1, even surpassing it by 7.6% at Moncompu. Treatments T2 and T3 generally incurred yield penalties (10–28%), except at Karaikal, where T2 increased yield (+5% in 2023; +11.6% in 2024), due to favorable decomposition conditions. Despite yield trade-offs, T2 and T3 (50% RDF substitution via crop residue) exhibited superior yield stability across locations. Soil nutrient dynamics varied considerably by location and treatment. While T2 and T3 caused partial phosphorus (P) depletion, they consistently improved soil potassium (K) and organic carbon (OC). P buildup was seen in T2/T5 at Karaikal and T1-T5 at Pusa. Similarly, K buildup was seen across most treatments and sites, though K mining was widespread at Pantnagar. Nitrogen (N) and OC showed mixed results, with some treatments leading to accumulation and others depletion. The T6 consistently showed the highest nutrient depletion across all parameters. T1 yielded the highest partial factor productivity of nitrogen (PFP-N) at 47 kg grain/kg N, closely followed by T5 (44 kg grain/kg N). T3 (42.5 kg grain/kg N) was statistically similar to T5, establishing a PFP-N hierarchy of T1 > T5 ≈ T3 > T2 ≈ T4. Grain yield correlated positively with agronomic traits like tiller number, panicle density, and 1000-grain weight, all linked to N and K availability. Thus, co-application of 75% RDF via fertilizers and 25% using crop residues with microbial decomposers (T5) is recommended as a sustainable alternative integrated approach to conventional fertilization.